THE FEATURES OF CLINICAL COURSE, DIAGNOSIS AND TREATMENT OF LITTRE'S HERNIA - V.I. Lyakhovskyi; M.O. Dudchenko; T.V. Horodova-Andrieieva; A.V. Sydorenko; P.V. Savchuk (Проблеми екології та медицини)
Among the complications of Meckel's diverticulum, which are rare, it is necessary to note Littre's hernia – the strangulation in the external abdominal hernia and its location in the hernia’s sac. Meckel's diverticulum is a protrusion of the wall of the ileum, which is formed as a result of incomplete obliteration of the bile duct, which is involved in embryotrophy. It occurs most often in inguinal and femoral hernias. This pathology is rarely observed in clinical practice, therefore, we present the clinical case of Littre's hernia. The aim of this research is to describe the features of the clinical course, diagnosis, and treatment of Littre's hernia, as well as to draw attention to the existence of such a disease. Clinical case. Patient V., born in 1960, was urgently admitted to the surgical department on January 19, 2022, with a diagnosis of “Strangulation of the left inguinal hernia”. On admission, he complained of acute pain in the protrusive area of the left inguinal zone. From the anamnesis: he had felt acute symptoms about two hours before admission. He had been noticing a bulge in the left inguinal area for 20 years. The patient was examined at the department and urgently operated on under spinal anesthesia. We conducted the resection of Meckel's diverticulum with allohernioplasty by Lichtenstein on the left. Postoperative diagnosis: strangulated left-sided inguinal hernia with strangulation of Meckel's diverticulum of the small intestine (Littre's hernia). The course of the postoperative period was uneventful. He was discharged from the hospital on the 7th day in satisfactory condition. At the time of discharge, the postoperative wound healed with primary tension. The patient was examined after 2 months: there were complaints of minor pain in the area of the postoperative wound during physical activity. The postoperative scar is in satisfactory condition. Thus, Littre's hernia is a rare surgical disease and is subject to urgent surgical treatment. At the same time, the scope of surgical treatment is determined during the operation and assessment of the condition of the intestine and diverticulum.